2001
DOI: 10.1385/endo:15:3:323
|View full text |Cite
|
Sign up to set email alerts
|

Adrenalectomy Regulates Apoptotic-Associated Genes in Rat Hippocampus

Abstract: Morphological studies of granular neurons of the hippocampus have shown that adrenalectomy (ADX) induces the cell death of granular neurons, an effect prevented by corticosterone replacement. We addressed the hypothesis that corticosterone regulates the expression of the apoptotic bcl-2 gene family. Five days after adrenalectomy, we observed morphological changes related to hippocampal granule cell apoptosis that was accompanied by terminal dUTP nick and labeling (TUNEL) labeling in nuclei located in the hilus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 48 publications
0
22
0
Order By: Relevance
“…Whole hippocampal homogenates were prepared as described earlier (Greiner et al, 2001;Andres et al, 2006). Seventy-five micrograms of protein from each homogenate were resolved by electrophoresis on 12% SDS-polyacrylamide gels, and electrotransferred onto 0.22-mm nitrocellulose membranes.…”
Section: Immunoblot Analysismentioning
confidence: 99%
“…Whole hippocampal homogenates were prepared as described earlier (Greiner et al, 2001;Andres et al, 2006). Seventy-five micrograms of protein from each homogenate were resolved by electrophoresis on 12% SDS-polyacrylamide gels, and electrotransferred onto 0.22-mm nitrocellulose membranes.…”
Section: Immunoblot Analysismentioning
confidence: 99%
“…Slightly elevated levels of CORT in plasma (200–270 nM range) in the rat have been reported to attenuate N-methyl-D-aspartate (NMDA) and amyloid-β toxicity, while chronic elevation (310–650 nM range) potentiated the neurotoxic effects in the nucleus basalis magnocellularis (Abraham et al, 2006). Moreover, absence of CORT for 3 days due to adrenalectomy (ADX) can result in apoptosis of granule cells of the dentate gyrus (DG) in adult rats (Greiner et al, 2001). Reduction of CORT in ad libitum fed rats by ADX produced hypophagia and satiety (Torres et al, 2008) and decreased locomotor activity (Duclos et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it is also found that the replacement of corticosterone can prevent the reduction of bcl-2 gene expression after ADX [86] . Secondly, it has been found that corticosterone can facilitate and enhance memory consolidation [87] .…”
Section: Dr and Corticosteronementioning
confidence: 95%
“…Firstly, the physiological level of corticosterone is critical for neuronal survival. Adrenalectomy (ADX), which means removal of the major organism for synthesizing corticosterone, can induce cell death of granular neurons in the hippocampus, while replacement of corticosterone could then block this neuronal death [86] .…”
Section: Dr and Corticosteronementioning
confidence: 99%